Dairy manure acidification reduces CH4 emissions over short and long-term. Issue 18 (11th August 2021) - Sokolov, Vera K.; VanderZaag, Andrew; Habtewold, Jemaneh; Dunfield, Kari; Wagner-Riddle, Claudia; Venkiteswaran, Jason J.; Crolla, Anna; Gordon, Robert
ABSTRACT: Acidification with sulphuric acid and cleaning residual manure in tanks are promising practices for reducing methane (CH4 ), which is a potent greenhouse gas. To date, no data are available on CH4 reductions from acidifying only residual manure (rather than all manure). Moreover, long-term effects of manure acidification (i.e. inoculating ability of previously acidified residual manure in the subsequent storages) are not known. To address these gaps, fresh manure (FM; 150 mL) combined with treated or untreated inoculum (30 mL) were anaerobically incubated at 17°C, 20°C, and 23°C for 116 d. Acidified treatments, regardless of location of acid addition, reduced CH4 production by 81% at 17°C, 78% at 20°C, and 19% at 23°C compared to the control (untreated FM and untreated inoculum). To test long-term acidification effects, FM was inoculated with manure that had been acidified 6-months prior. This created comparable CH4 production to FM with no inoculum and reduced CH4 production by 99% at 17°C and 20°C, and 49% at 23°C compared to the control. Results indicate that residual slurries of acidified manure become poor inoculants in subsequent storage, hence manure acidification has a long-term treatment effect in reducing CH4 production. This could reduce how often acidification is needed in dairy manure tanks and also increasing its cost-effectiveness for farmers. GRAPHICAL ABSTRACT: UF0001